Soetsu Yanagi selected essays on Japanese folk crafts - Yanagi, Muneyoshi 1889-1961; Brase, Michael; Nihon Mingeikan (2017)
"The common utilitarian objects depicted in this book were considered aesthetically insignificant until the appearance of Soetsu Yanagi. It was Yanagi who discovered the beauty that could only be produced by simple, humble craftsmen repeatedly and unselfconsciously working on the same objects day after day. From this quotidian world emerged a distinctive beauty - wholesome, free, and devoid of self-awareness. To bring these crafts to the notice of the world, Yanagi established the Japan Folk Crafts Museum in 1936, from whose collection the objects illustrated herein have been chosen for inclusion by the publisher. In the essays, Yanagi expounds his philosophy of folk crafts and highlights particular pieces. Altogether, the book constitutes a penetrating insight into the world of Japanese handicrafts"--Publisher's website.
Textiles -- Ceramics -- Wood and lacquer -- Metal -- Sculpture -- Pictorial art -- What is folk craft? -- The beauty of miscellaneous things -- A painted Karatsu as food for thought -- What is pattern? -- Okinawa's Bashofu -- The beauty of Kasuri -- The characteristics of Kogin -- The Japanese perspective -- The story behind the discovery of Mokujiki -- Woodblock prints -- Otsu-e -- Handicrafts and sesshu -- Washi -- Seeing and knowing -- A letter to my Korean friends -- The Japan Folk Crafts Museum.
The essays appearing in this book were selected from Yanagi Soetsu korekushon 2: mono (Chikuma Shobo; chapters 2-7, 10-14) and Mingei yonju-nen (Iwanami Shoten; chapters 1,8,9,15,16)--verso of the title page.
Japan Foundation
Translated from the original Japanese into English.
Keywords: Yanagi, Muneyoshi -- 1889-1961 -- Translations into English; Folk art -- Japan; Decorative arts -- Japan